2021
DOI: 10.1088/1742-6596/1808/1/012029
|View full text |Cite
|
Sign up to set email alerts
|

Investigating of the Relations among TPACK Components of Economic Teacher Candidates in Sebelas Maret University (UNS) in 2020: A Structural Equation Modeling

Abstract: This study examines the structural relationship between the components in TPACK. The sample of this study was 98 economics teacher candidates at Sebelas Maret University Surakarta, Indonesia. This research design is quantitative with structural equation modeling (SEM) analysis techniques. The results of this study indicate that the questionnaire is valid and reliable and the hypothesis shows that there is a significant influence between the TPACK components except TK, PK, and CK on TPACK. The results of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…According to Pamuk et al (2013), TPACK relationships are as follows: (a) second-layer knowledge bases (PCK, TCK, TPK) predict TPACK better than core knowledge bases (TK, PK, CK), (b) TCK, followed by TPK, is the strongest predictor of TPACK, (c) core knowledge bases indirectly influence TPACK, via second-layer knowledge, (d) core knowledge bases are correlated with their intersected knowledge (i.e., TK impacting TCK and TPK, CK impacting PCK and TCK, PK impacting PCK and TPK). These findings are fully supported by Santika et al (2021) with their recent study examining structural relationships between TPACK components. Other researchers agreed on most yet opposed some of the above findings.…”
Section: Literature Reviewsupporting
confidence: 72%
See 2 more Smart Citations
“…According to Pamuk et al (2013), TPACK relationships are as follows: (a) second-layer knowledge bases (PCK, TCK, TPK) predict TPACK better than core knowledge bases (TK, PK, CK), (b) TCK, followed by TPK, is the strongest predictor of TPACK, (c) core knowledge bases indirectly influence TPACK, via second-layer knowledge, (d) core knowledge bases are correlated with their intersected knowledge (i.e., TK impacting TCK and TPK, CK impacting PCK and TCK, PK impacting PCK and TPK). These findings are fully supported by Santika et al (2021) with their recent study examining structural relationships between TPACK components. Other researchers agreed on most yet opposed some of the above findings.…”
Section: Literature Reviewsupporting
confidence: 72%
“…Several investigations note it as the strongest predictor of technology integration (Aslan & Zhu, 2017;Ertmer et al, 2012). Previous literature usually employs the Technology Pedagogical Content Knowledge (TPACK) theory to investigate teacher knowledge required to integrate technology in instruction (Joo et al, 2018;Raper, 2018;Santika et al, 2021;Yang et al, 2019). According to the theory, teacher knowledge includes content knowledge (CK), pedagogical knowledge (PK), technological knowledge (TK), pedagogical content knowledge (PCK), technological content knowledge (TCK), technological pedagogical knowledge (TPK), and technological pedagogical content knowledge (TPACK).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationships of TPACK constructs have been manifested in some of the quantitative studies that examined the influences of TK, PK, CK, and intermediary factors (i.e., PCK, TCK, and TPK) on TPACK (Chai et al, 2010;Chai et al, 2012;Koh et al, 2013;Pamuk et al, 2015;Santika et al, 2021). Underpinned by the TPACK framework, the importance of investigating the relationships of TPACK-G constructs arises.…”
Section: Technological Pedagogical Content Knowledge Of Digital Games...mentioning
confidence: 99%
“…Previous research indicated the importance of understanding the relationships and developmental paths among TPACK constructs for teachers' TPACK development processes (Hsu et al, 2015;Santika et al, 2021). For TPACK-G, there is limited research addressing the relationships of TPACK-G constructs (Hsu et al, 2017), and a lack of research on TPACK-G in the context of pre-service teachers.…”
Section: Introductionmentioning
confidence: 99%